2022
DOI: 10.3390/ijerph192013680
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Self-Reports of How Adolescent Substance Use Changed with the COVID-19 Pandemic

Abstract: The final year of high school is a challenging phase of adolescents’ lives and substance use can play an important role. We examined changes in the frequency and quantity of alcohol and cannabis use, and demographic correlates among Grade 12 students of 2020. Students (N = 844) from nine schools retrospectively self-reported changes in substance use after the easing of COVID-19 lockdowns (back to school), compared to before the pandemic. Changes in use were examined with age, gender, Aboriginal or Torres Islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A recent systematic review concluded that THC administered orally has a variable pharmacokinetic profile, which differs between formulations, with high variability, including in the case of similar formulations [ 30 ]. Furthermore, data on the demographic-specific impact of cannabis use [ 29 , 31 , 32 , 33 ], substance use disorders [ 34 , 35 , 36 ], abuse, dependence and risks come only from retrospective reports [ 37 , 38 ]. Therefore, randomized controlled trials on standardized GMP-level cannabis products are needed to reduce the results’ unpredictability when using medical cannabis, to increase the efficacy and safety of compound formulations for therapeutic uses, and to support further investigations regarding the use of cannabis in specific conditions and pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review concluded that THC administered orally has a variable pharmacokinetic profile, which differs between formulations, with high variability, including in the case of similar formulations [ 30 ]. Furthermore, data on the demographic-specific impact of cannabis use [ 29 , 31 , 32 , 33 ], substance use disorders [ 34 , 35 , 36 ], abuse, dependence and risks come only from retrospective reports [ 37 , 38 ]. Therefore, randomized controlled trials on standardized GMP-level cannabis products are needed to reduce the results’ unpredictability when using medical cannabis, to increase the efficacy and safety of compound formulations for therapeutic uses, and to support further investigations regarding the use of cannabis in specific conditions and pathologies.…”
Section: Introductionmentioning
confidence: 99%